Reduce Power Quality Problems Owing to Nonlinear Loads in Electric Grid Systems Using Series APF (International Journal of Food and Nutritional Sciences, 2022)
An essential indicator of an electrical powersystem's performance is power quality.Furthermore, issues with the utility grid, likevoltage harmonics, imbalances, and swells, havecontributed to a reduction in the power qualityrequired for important loads